The incorporation of alpha-tocopherol and functional doses of phytosterol esters during cheesemaking does not affect DNA or mRNA dynamics of Streptococcus thermophilus and Lactococcus lactis throughout and after the end of ripening. (October 2017) - Pega, J.; Pérez, C.D.; Rizzo, S.; Rossetti, L.; Díaz, G.; Ruzal, S.M.; Nanni, M.; Descalzo, A.M.
Abstract: Tocopherols and phytosterols are lipid-soluble molecules which have been widely used in the food industry. Nevertheless, the influence of these compounds on the performance of starter lactic acid bacteria (SLAB) in fermented foods has received little attention. Here, we assessed the behavior of Streptococcus thermophilus and Lactococcus lactis during the ripening of a functional Port Salut light cheese elaborated with these SLAB and with alpha-tocopherol and phytosterol esters as bioactive molecules. Functional and control cheeses were manufactured at an industrial plant and sampled at 7, 21, 40, 60 and 90 days after elaboration for real-time quantitative PCR (qPCR) or reverse transcription-qPCR (RT-qPCR) experiments. Target DNA and mRNA from both SLAB were detected after 90 days of elaboration in both functional and control cheeses, supporting their potential role in generating flavor metabolites. Furthermore, here we showed for the first time that the addition of alpha-tocopherol and functional doses of phytosterols did not affect DNA or mRNA dynamics of these SLAB during cheesemaking, throughout and after the end of ripening. Therefore, our results support the use of cheese manufactured with both S. thermophilus and L. lactis as an optimal delivery system for these beneficial bioactive compounds. Highlights: We produced industrial cheeses with alpha-tocopherol and functional phytosterols. Streptococcus thermophilus and Lactococcus lactis were used as starter bacteria. DNA and mRNA from both bacteria persisted after the end of ripening (90 days). The bioactive molecules did not affect the behavior of the bacteria during ripening.